2021
DOI: 10.1080/1369118x.2020.1864005
|View full text |Cite
|
Sign up to set email alerts
|

Is there a link between climate change scepticism and populism? An analysis of web tracking and survey data from Europe and the US

Abstract: He has interests in virtual environments, the social aspects of e-science, and the sociology of science and technology. He has written extensively about virtual reality technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…On the one hand, this concerns the use of these methods for data retrieval , for instance scholars acquiring “big data” via crawling, scraping, or by relying on Application Programming Interfaces (APIs). Computational methods have been used … to collect data on how organizational and individual, professional and non‐professional communicators position themselves towards climate change by using transcripts of national parliamentary debates (Majdik, 2019), crawling websites and social media accounts of influential stakeholders (Adam et al, 2020), or scraping websites hosting policy documents (Biesbroek et al, 2020); to collect data on how public communication about climate change is structured by using programming scripts to access databases on news coverage (Buckingham et al, 2020) or social media platforms (Pearce et al, 2014); or to collect data on audience behavior towards climate change by relying on Google search trends (Le Nghiem et al, 2016), individual users' social media content (Williams et al, 2015), or digital traces from web tracking (Yan et al, 2021). …”
Section: Computational Methods For the Analysis Of Climate Change Com...mentioning
confidence: 99%
“…On the one hand, this concerns the use of these methods for data retrieval , for instance scholars acquiring “big data” via crawling, scraping, or by relying on Application Programming Interfaces (APIs). Computational methods have been used … to collect data on how organizational and individual, professional and non‐professional communicators position themselves towards climate change by using transcripts of national parliamentary debates (Majdik, 2019), crawling websites and social media accounts of influential stakeholders (Adam et al, 2020), or scraping websites hosting policy documents (Biesbroek et al, 2020); to collect data on how public communication about climate change is structured by using programming scripts to access databases on news coverage (Buckingham et al, 2020) or social media platforms (Pearce et al, 2014); or to collect data on audience behavior towards climate change by relying on Google search trends (Le Nghiem et al, 2016), individual users' social media content (Williams et al, 2015), or digital traces from web tracking (Yan et al, 2021). …”
Section: Computational Methods For the Analysis Of Climate Change Com...mentioning
confidence: 99%
“…In addition to political elites, news media, particularly conservative news media and far-right populism media, are institutional sources that influence the production and circulation of anti-intellectual discourses on social media. Although anti-intellectual discourse is likely to appear in both left- and right-wing news media, Yan et al (2021) found that science skeptics were mostly associated with far-right populism websites. The far-right media often claim themselves as the alternative media, which are “corrective of ‘traditional,’ ‘legacy,’ or ‘mainstream’ news media in a given sociocultural and historical context” ( Holt et al, 2019 : 862).…”
Section: The Constructions Of Anti-intellectual Discourses On Twittermentioning
confidence: 99%
“…As for media-level variables, we were interested in the topic of the URL identified by means of a keyword search within the URL and this included international trade, immigration, citizenship, and cultural diversity. Media type, as mentioned in the previous section, was coded by team members of the research project [Stier et al, 2020;Yan et al, 2021] and included six media categories: commercial broadcast, digitalborn news outlet, hyper-partisan media, public service broadcast, quality newspaper or magazine, and tabloid news websites.…”
Section: Web Tracking Datamentioning
confidence: 99%
“…The rise and fall of public attention to online news about social issues such as climate change is often influenced by offline events [Yan et al, 2021]. Attention to globalisation related news websites was measured here by calculating average time spent on a globalisation related news website per panellist.…”
Section: Public Attention To Globalisation Related News Content Onlinementioning
confidence: 99%